Development of SETS (Science Environment Technology and Society) Based E-Modules on Environmental Pollution Materials to Increase Learning Interest and Critical Thinking Ability - Resti Yevira; Yustina; Yennita (Jurnal Penelitian Pendidikan IPA, 2023)
The background of this research stems from the minimal number of learning resources E-module Science E-module for class VII SMP, learning activities which are still monotonous and are still little used, there is a dichotomy of science and a learning model that is still teacher-centered which is synonymous with lectures, there is no module that contains SETS values, and UN results that do not meet the KKM on environmental pollution. The objectives of this research are: (1) Development of IPA E-module products. (2) Knowing the feasibility of the SETS-based IPA E-module, (3) Knowing the effectiveness of the application of SETS-based IPA modules. The product developed in this study is the SETS-based IPA E-module. Specifications for the science module in the form of printed media as a competency-based 2013 implementation curriculum. The subjects in this study were class VII students of junior high school. The sample consisted of teachers belonging to the Siak MGMP, and class VII students of SMP Nurul Furqon Siak. The validity test of the developed module can be seen from the validity test using the Pearson product moment test using SPSS 25 for windows software and so that the questionnaire used in this research is truly reliable as a data collection tool and can see the concentration of the questionnaire used, the questionnaire is tested for reliability or the level of trust can carry out Cronbach's alpha inferential test with the help of SPSS.The data analysis technique used is descriptive qualitative. The conclusion of this research is; First, SETS-based Science E-Module Development on environmental pollution material. Second, the development of SETS-based Science E-Modules can be said to be very practical in terms of the material aspect 3.25 the presentation is very good in language and graphics is very good so that it can be interpreted that the modules developed are said to be very good for use in science learning. Third, the development of well-developed SETS-based Science modules is effectively used to improve student learning outcomes. So it can be concluded that learning outcomes using SETS-based science modules are better than conventional learning.